Bus Griffiths' Now You're Logging: A Graphic Novel about British Columbia Coastal Logging in the 1930s - Hak, Gordon H. (Gordon Hugh) (Labour / Le Travail, 2005)
A comic book is an unlikely entrée into the history of logging in coastal British Columbia, but Bus Griffiths’ 1978 graphic novel "Now You’re Logging" provides an intriguing window onto work in the woods in the 1930s. Griffiths worked for years as a logger on the coast, experiencing the camps of the 1930s directly. ..."Now You’re Logging" offers a particular version of the loggers’ life, but it still captures many aspects of work in the coastal forests of the 1930s, and does so in an accessible manner. There are many popular histories of British Columbia coastal logging, chock full of photographs, but Griffiths offers black-and-white drawings, and, as bird watchers inspecting field guides know, drawings often provide a more effective way of presentation. As a work of fiction it stands comfortably with other narratives, such as Haig-Brown’s "Timber" and Martin Allerdale Grainger’s "Woodsmen of the West," in giving helpful perspectives on the history of the loggers’ world. --From author's introduction and conclusion